Bile Reflux Gastritis in Patients with Chronic Heartburn: Prevalence, Pathophysiology, and Clinical Relevance - Amira Sameh Abdelkader, Sameh M. Abdel Monem , Ibrahim M. Ibrahim , Ola A. Harb , Mai Saad Ghanem (Cuestiones de Fisioterapia, 2024)
Chronic heartburn is a prevalent gastrointestinal complaint traditionally attributed to acid-mediated gastroesophageal reflux disease (GERD). However, increasing evidence suggests that non-acid components, particularly duodenogastric bile reflux, play a significant yet under recognized role in the pathogenesis of persistent upper gastrointestinal symptoms